RESPON BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI PRE NURSERY PADA MEDIA ULTISOL YANG MENDAPAT APLIKASI SLUDGE DAN PUPUK PELENGKAP CAIR - Jauhari, Putra Amir; Armaini, Armaini; Ikhsan, Al (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study aims to determine the effect of sludge and liquid manure as well as to obtain the best dose of sludge and liquid fertilizer for the growth of oil palm seedlings in ultisol media. Research conducted at the Experimental Farm, Faculty of Agriculture, University of Riau Pekanbaru. The study was conducted during the four months from April to August 2015. The study conducted an experiment using a completely randomized design (CRD) with 2 factors and 3 replications. The first factor is the sludge (S), which consists of 4 levels and the second factor is fertilizer complementary liquid (P) consisting of 3 levels. Comparisons between treatment parameters observed were seedling height, number of leaves, the girth, shoot to root ratio, root volume, seedlings dry weight using ANOVA and Duncan's multiple range test level of 5%. The results showed that the application of sludge and PPC has no significant effect on seedling height, number of leaves, girth, shoot to root ratio, seedling dry weight and root volume. Sludge 75 g / polybag and PPC 4 cc / l applications on pre nursery oil palm seedlings in ultisol media tend to improve seedling height, number of leaves, wrap tubers, roots canopy ratio, seedling dry weight and root volume. Keyword : Coconut Oil, Sludge, Fertilizer Complement Liquid, Ultisol